Teaching physics through contextualized concept cartoons - Reyes-Roncancio , Jaime Duvan; Romero-Osma, Gloria Patricia; Bustos-Velazco, Edier Hernan (Revista Científica, 2019)
This document present the results of a research in the use of Cartoon in teaching of physics. The methodology of mixed approach, involved at first the design and use of Concept Contextualized Cartoons, as well their validation and implementation among groups of high school students. Secondly, a motivational scale regarding the use of cartoons and the teaching of physics was adapted and applied. The results describe the characteristics of the questions formulated by the students when interacting with the cartoon, specifically in relations the scientific knowledge associated to three phenomena of study: Atmospheric Electric discharges – Thunderbolt, Electric Current and Polarization. Furthermore, the cartoons didactic potential was identified in relation to the categories of the motivational scale, which highlights significant motivational levels associated with the relationship with life and the importance of the physics class.